Biomechanical effects of different numbers and locations of screw-in clavicle hook plates - Wang, Cheng-Chi; Lee, Cheng-Hung; Chen, Kun-Hui; Pan, Chien-Chou; Tsai, Ming-Tzu; Su, Kuo-Chih (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: We sought to analyze the biomechanical effects which both different numbers and locations of screws have on three different clavicle hook plates, as well as any possible causes of sub-acromial bone erosion and peri-implant clavicular fractures. Methods: This study built thirteen groups of finite element models using three different clavicle hook plates (short plates, long plates, and posterior hook offset plates) in varying numbers and locations of the screws. The von Mises stress distribution of the clavicle and hook plate, as well as the reaction force of the acromion was evaluated. Results: The results show that inserting screws in all available screw holes on the hook plate produces a relatively large reaction force on the acromion, particularly in the axial direction of the bone plate. The fewer the screws implanted into the clavicle hook plate, the larger the area of high-stress distribution there is in the middle of the clavicle, and also, the higher the stress distribution on the clavicle hook plate. Conclusion: This study provides orthopedic physicians with the biomechanical analysis of different numbers and locations of screws in clavicle hook plates to help minimize surgical complications.